Hubungan Gaya Berpacaran dan Paparan Pornografi terhadap Perilaku Seksual Berisiko Remaja di SMA Negeri 2 Kupang Timur - Maria Roswita Seran; Christina R. Nayoan; Eryc Z. Haba Bunga; Marni, Marni (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Adolescence is a period characterized by many changes within individuals, including a curiosity about sexuality. Risky sexual behavior in teenagers can be influenced by risky dating styles and exposure to pornography. This study aims to investigate the relationship between dating styles and pornography exposure on risky sexual behavior among students at SMA Negeri 2 Kupang Timur. The research employed a quantitative method with a cross-sectional design. The population in this study consists of students in grades X and XI at SMA Negeri 2 Kupang Timur, with a sample size of 76 respondents selected using proportional stratified random sampling techniques. The research results show that the majority of respondents have a healthy dating style at 73.7%, are not exposed to pornography at 52.6%, and have low-risk sexual behavior at 81.6%. The bivariate analysis using the Chi Square test shows a relationship between dating style (p-value=0.000) and exposure to pornography (p-value=0.001) on risky sexual behavior. The study at SMA Negeri 2 Kupang Timur indicates that teenagers with unhealthy dating styles and high access to pornography content are more likely to engage in risky sexual behavior. It is hoped that teenagers can actively participate in positive activities to divert attention from pornography exposure and build healthy relationships.